The Centenary of the Polish Studies at the University of Vilnius - Dalecka, Teresa (Slavistica Vilnensis, 2018)
[full article, abstract in Polish; abstract in Lithuanian and English] The aim of this article is to present professors and their most prominent graduates of Polish Philology Department from the Stefan Batory University and to outline the history of Polish studies operating at the University of Vilnius from 1993. The last 25 years of Polish philology has been a continuation of the glorious inter-war traditions where Vilnius’ philologists – along with others from Warsaw, Cracow, Poznan, Lublin and Lviv – created a thriving scientific community. The scholars’ personalities who worked at SBU determined the direction of research and didactics development. They understood social service as wide dissemination of science and culture. This formed a new type of academic teachers who combine the qualities of a scholar and knowledge spreader. The same exact ideals are guided today by the employees of the Centre of Polish Studies at the University of Vilnius.